Pengaruh Kemampuan Kerja, Pengalaman dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT. Amerta Bangun Persada Kediri - Muhammad Ifshokhul Anam; Brahma Wahyu K; Aprilia Dian Evasari (Jurnal Publikasi Ilmu Manajemen, 2023)
This research aims to find out and explain the results of the influence of work ability, experience and work discipline on employee performance at PT. Amerta Bangun Persada Kediri. This research uses quantitative descriptive methods. This research uses all employees at PT. Amerta Bangun Persada Kediri. The sample used in this research was PT workers. Amerta Bangun Persada Kediri has 39 workers. The sampling method used in this research is saturated sampling. Data processing in this research includes Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, T Test, F Test, and Coefficient of Determination Test (R2). The results of this research are that work ability has no partial influence on employee performance with a significant value of 0.947 > 0.05. Experience has no partial influence on employee performance with a significant value of 0.350 > 0.05. Work discipline has a partial influence on employee performance with a significant value of 0.020 < 0.05. Work ability, experience and work discipline simultaneously have an influence on employee performance with a significant value of 0.03 < 0.05. So that PT. Amerta Bangun Persada Kediri must improve further. Work ability, experience and work discipline for all workers so that they are able to optimize the performance of each worker effectively and efficiently when entrusted with the obligations and responsibilities of the company.